Kontribusi yang Dipersepsikan dari Desain Biofilik terhadap Kualitas Hidup: Inversi Kontekstual Elemen Air dan Risiko pada Permukiman Padat Pesisir - Aissyah Nabila Anjani; Prananda Navitas (Dinasti Research, 2026)
This article examines the perceived contribution of biophilic design elements to quality of life and the contextual inversion of water and risk in a high-density coastal settlement along MT Haryono Street, Pasuruan City. A descriptive-analytical approach was employed using a survey of 96 residents selected through cluster sampling. Fourteen biophilic design patterns were assessed through a five-point Likert scale across six perceived quality-of-life dimensions. The data were analysed using frequency distributions, mean scores, and contextual interpretation supported by field observations. Visual connection with nature obtained the highest mean score (4.66), followed by thermal and airflow variability (4.65) and dynamic and diffuse lighting (4.65). These findings indicate that residents most strongly value elements whose benefits are directly experienced through greenery, fresh air, thermal comfort, and natural light. Presence of water received a moderate score (3.52), but its meaning was ambivalent because water was also associated with stagnant water, inadequate drainage, unpleasant odours, and tidal flooding. Risk and peril received the lowest mean score (2.15), showing that risk was not perceived as a controlled and pleasurable spatial experience but as an environmental threat. The study concludes that biophilic design in dense coastal settlements must be selective and context-sensitive, prioritising functional and safe interventions rather than universally transferring biophilic patterns from formal urban settings.